High-resolution time-of-flight PET detector with 100 ps coincidence time resolution using a side-coupled phoswich configuration. (9th June 2021) - Lee, Min Sun; Cates, Joshua W; Gonzalez-Montoro, Andrea; Levin, Craig S
Abstract: Photon time-of-flight (TOF) capability in positron emission tomography (PET) enables reconstructed image signal-to-noise ratio (SNR) improvement. With the coincidence time resolution (CTR) of 100 picosecond (ps), a five-fold SNR improvement can be achieved with a 40 cm diameter imaging subject, relative to a system without TOF capability. This 100 ps CTR can be achieved for a clinically relevant detector design (crystal element length ≥20 mm with reasonably high crystal packing fraction) using a side-readout PET detector configuration that enables 511 keV photon interaction depth-independent light collection efficiency and lower variance in scintillation photon transit time to the silicon photomultiplier (SiPM). In this study, we propose a new concept of TOF-PET detector to achieve high (<2 mm) resolution, using a 'side-coupled phoswich' configuration, where two crystals with different decay times ( τ d ) are coupled in a side-readout configuration to a common row of photosensors. The proposed design was validated and optimized with GATE Monte Carlo simulation studies to determine an efficient detector design. Based on the simulation results, a proof-of-concept side-coupled phoswich detector design was developed comprising two LSO crystals with the size of 1.9 × 1.9 × 10 mm 3 with decay times of 34.39 and 43.07 ns, respectively. The phoswich crystals were side-coupled to the same three 4 × 4 mm 2 SiPMs and detector performances were evaluated. As a result of the experimental evaluation, the side-coupled phoswich configuration achieved CTR of 107 ± 3 ps, energy resolution of 10.5% ± 1.21% at 511 keV and >95% accuracy in identifying interactions in the two adjacent 1.9 × 1.9 × 10 mm 3 crystal elements using the time-over-threshold technique. Based on our results, we can achieve excellent spatial and energy resolution in addition to ∼100 ps CTR with this novel detector design.